Optimizing Data-Based Planning to Realize the Quality of Continuing Education at SDN Cileungsi 06 - Eis Naeni; Masduki Ahmad; Desi Rahmawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this research is to find and identify the root of the problem in Data-Based Planning that is useful for realizing the quality of sustainable basic education. In this study, the three elements that actively implement the program consist of teachers, principals, and learning communities. Analysis of Education Report data documents for school planning and reporting, as well as a review of learning community activities, are all strategies used to collect data. The results of the study show that the most effective methods to realize high-quality and sustainable education through the learning community are as follows: (1) using educational report card data as a basis for discussion and reflection, (2) using the Identification, Reflection, Improvement Planning, Improvement Implementation (IRBB) approach in solving the root of school problems, (3) allowing teachers to work together to learn through training, (3) incorporating learning community outcomes into educational planning in schools (RKT and RKAS), and (4) improving a culture of learning, sharing, collaboration and evaluation based on real practices.. The findings are expected that stakeholder collaboration and the learning community can be more than just an ordinary discussion space. Proper data-driven planning and community collaboration Learning can be recommended as a strategic effort to drive a sustainable transformation of quality-oriented school culture.